(untitled) - Pearson, Steven D.; Steven D. Pearson; James E. Sabin; Ezekiel J. Emanuel (Oxford,New York, 2003)
Can the ethical mission of health care survive among organizations competing for survival in the marketplace? On this question hinges not only the future of health care in the US, but that of the health care systems of all advanced countries. This book presents both an analytic framework and a menu of pragmatic answers...
Keywords: Managed care plans (Medical care); Health facilities; Medical ethics